(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Abortion in Bangladesh is illegal under most situations, but menstrual regulation is often used as a substitute. Abortion can be legally performed by a physician in a hospital if it is necessary to save the life of the mother. A person, who performs an abortion under any other circumstances, including a woman who self-aborts, can be punished by a fine and imprisonment. Objective: To assess the socio-demographic profile of abortion cases attending a tertiary level hospital of Bangladesh. Materials and Methods: This cross-sectional descriptive type of study was carried out among 80 patients at the Gynae ward and out patient department of Dhaka Medical College Hospital from March 2012 to June 2012. The study population was women attending the selected hospital for an abortion or abortion-related complications. Results: Most of the respondents 35(43.8%) were below 25 years of age and all patients were housewives. The maximum number of patients 63(78.8%) had spontaneous abortion, low socio-economic status and majority were multigravidas. It was also found that patients with abortion were mostly in their second (43.8%) and third (21.3%) decade of life. Conclusion: In this study, the commonest reason for termination of pregnancy was unplanned pregnancy. Creating awareness and timely intervention might decrease the number of abortion cases. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 200-202